Pengaruh Perubahan Tata Guna Lahan Terhadap Limpasan Permukaan Dan Erosi Lahan Daerah Aliran Sungai (DAS) Bendungan Temef Dengan Soil And Water Assessment Tool (SWAT+): The Impact Of Land Use Change On Surface Runoff And Soil Erosion In The Temef Dam Watershed Using The Soil And Water Assessment Tool (SWAT) - Arnoldus Nama; Yunus Fallo; Fabianus J. S. Nope (Media Ilmiah Teknik Sipil, 2026)
Land-use change is one of the primary drivers influencing watershed hydrological conditions. Uncontrolled conversion of land in the Benanain watershed, particularly in the Temef sub-watershed, has the potential to increase surface runoff and accelerate soil erosion, which in turn increases sedimentation within the Temef Dam reservoir. This study aims to analyze the impact of land-use changes between 2018 and 2024 on surface runoff and soil erosion using the Soil and Water Assessment Tool Plus (SWAT+). Data used include rainfall, climate, DEM, soil type maps, and land cover maps which were processed through watershed delineation, HRU formation, and hydrological simulations. The results indicate significant land-cover changes, particularly a reduction of shrubland by 27.65% and an increase in forest area by 23.74%. These changes significantly affect runoff patterns, where in 2024 sub-watershed 6 produced the highest annual runoff of 611.96 mm and sub-watershed 8 the lowest at 209.93 mm. The findings provide a comprehensive understanding of hydrological dynamics in the Temef watershed and serve as a scientific reference for soil-water conservation planning and sustainable watershed management.